Optimization of Education Through Booklets in Improving the Role of Cadres on Local Food Processing for Stunting Children - Lestari, Nur Eni; Herliana, Irma; Solehudin, Solehudin; Koto, Yeni; Lannasari, Lannasari (Indonesian Journal of Community Development, 2024)
Introduction: Situation analysis obtained in RW 05 Kertamaya Bogor Selatan are that there are 7 health cadres, but only 5 cadres are active. The results of the interview showed that the low role of these cadres was caused by a combination of various factors, ranging from limited knowledge, minimal educational facilities, lack of support, low community involvement, time problems, to low motivation. Objective: Optimizing education through booklets in increasing the role of cadres in processing local food ingredients for stunted children. Method: Problem solving is carried out through several steps. The first stage of preparation consists of initial preparation and planning. The preparation stage is by conducting a needs analysis by reviewing and collecting information through literature studies of related journals, conducting situation analysis through interview reviews, observations, and distributing questionnaires to cadres, and finding partner problems. While the planning stage is determining problem solutions, determining strategies, and planning activities; the second stage of implementation is conducting a knowledge test on participants before education is carried out, implementing the optimization of education through booklets in increasing the role of cadres in processing local food ingredients for stunted children, and conducting a post-test for participants after education. This second stage ends with an analysis of the process and test results. Conclusion: The results of the Community Service showed an increase in the role of cadres in processing local food ingredients for stunted children after community service was carried out, with the majority having a good role of 66.7%. The booklet helps cadres convey information more effectively, increases community understanding, and encourages local food independence.